(untitled) (Revista do Centro de Estudos Portugueses, 2008)
Este trabalho desenvolve o percurso intertextual do Gótico literário anglosaxão do século XVIII na escrita do romancista mineiro Lúcio Cardoso (1912- 1968), em seus vários desdobramentos, como a tese do feminino enquanto agente destruidor do patriarcalismo, as marcas do Gótico hollywoodiano, e os traços do vampirismo literário, em suas diversas manifestações. O desejo enquanto clausura e o pastiche intratextual convivem na narrativa cardosiana aqui estudada, que exibe o comparecimento, dialético, tanto da “verdade” da hermenêutica quanto da “mentira” da teatralização. This work traces the intertextual presence of eighteenth-century Anglo-Saxon Gothic literature in the writing of Brazilian novelist Lúcio Cardoso (1912- 1968), in its many unfoldings, such as the thesis of the female as the destroyer of patriarchalism, the trappings of Hollywood Gothic, and the marks of literary vampirism in its several manifestations. The concept of desire as imprisonment and the intratextual pastiche go hand in hand in the “cardosian” narrative here studied, which exhibits the dialectic presence of both the “truth” of Hermeneutics and the “deception” of theatricality.